2017
DOI: 10.1038/s41598-017-06857-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of aberrant crypt foci in the human colon targeting glutathione S-transferase P1-1

Abstract: Aberrant crypt foci (ACF), the earliest precursor lesion of colorectal cancers (CRCs), are a good surrogate marker for CRC risk stratification and chemoprevention. However, the conventional ACF detection method with dye-spraying by magnifying colonoscopy is labor- and skill-intensive. We sought to identify rat and human ACF using a fluorescent imaging technique that targets a molecule specific for ACF. We found that glutathione S-transferase (GST) P1-1 was overexpressed in ACF tissues in a screening experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…To quantify the fluorescence intensity, regions of interest (ROIs) with a diameter of 7 mm were selected in each tumor and the background skin, and the fluorescence intensities were calculated using software provided by the manufacturer. The signal to noise (S/N) ratio was calculated as described previously 23 .…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the fluorescence intensity, regions of interest (ROIs) with a diameter of 7 mm were selected in each tumor and the background skin, and the fluorescence intensities were calculated using software provided by the manufacturer. The signal to noise (S/N) ratio was calculated as described previously 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Just recently, Muguruma and co-workers found that glutathione Stransferase (GST) P1-1 is overexpressed in ACF tissues and synthesized the fluorogenic probe DNAT-Me which is activated by GST P1-1. 39 When DNAT-Me was sprayed onto colorectal mucosa excised from AOM-treated rats and specimens from CRC patients, ACF with strong fluorescent signals were clearly observed with the advantage of a higher signal-to-noise ratio for ACF in DNAT-Me imaging compared to preoperative methylene blue staining. 39 In addition to visualization of colorectal adenomas or direct precursor lesions of CRC such as AFI, a variety of studies has Digestive Endoscopy 2018; 30: 730-738 Molecular imaging within the lower GI-tract 735 successfully provided proof of concept that molecular imaging can also visualize CRC and cancer cells.…”
Section: Molecular Imaging Of Sporadic Colorectal Cancermentioning
confidence: 97%
“…With aberrant crypt foci (ACF) as the earliest precursor lesion of CRC, ACF might act as surrogate markers for CRC risk stratification and chemoprevention. Just recently, Muguruma and co‐workers found that glutathione S‐transferase (GST) P1‐1 is overexpressed in ACF tissues and synthesized the fluorogenic probe DNAT‐Me which is activated by GST P1‐1 . When DNAT‐Me was sprayed onto colorectal mucosa excised from AOM‐treated rats and specimens from CRC patients, ACF with strong fluorescent signals were clearly observed with the advantage of a higher signal‐to‐noise ratio for ACF in DNAT‐Me imaging compared to preoperative methylene blue staining …”
Section: Components Of Molecular Imagingmentioning
confidence: 99%
“…In addition, enzymes such as glutathione S-transferase-P1 (GST-P1) in the cytosol, Îł-glutamyl transpeptidase (GGT) in cell membranes, and cathepsin in lysosomes are highly expressed in certain tumor cell types including colorectal tumors [9, 10]. Molecular imaging studies using a fluorogenic substrate probe, which is fluorescently quenched but activatable by enzyme activity only in the tumor cells, have been reported [11, 12].…”
Section: Targets Of Molecular Imaging In Colorectal Tumorsmentioning
confidence: 99%
“…ACF is the earliest form of colorectal tumor lesion, which shows dense staining with methylene blue and is detectable by stereomicroscopy or magnifying endoscopy [21]. Employing a fluorogenic probe (DNAT-Me) activated by GSTP1-1, we performed molecular imaging of ACF, colorectal adenoma, and CRC in an AOM-induced rat carcinogenesis model and in human colorectum ex vivo [11]. DNAT-Me is a fluorescently quenched substrate but is activated by GSTP1-1 in tumor cells to release a strong fluorophore.…”
Section: Molecular Imaging Of Colorectal Tumors In Animalsmentioning
confidence: 99%